2008
DOI: 10.1007/s10826-008-9222-1
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Adolescents’ Attitudes Toward Their Fathers and Loneliness: A Cross-Cultural Study

Abstract: Loneliness can be regarded as an epidemic of modern society that is becoming increasingly problematic for millions of people. Adolescents are particularly susceptible to the development of this kind of emotional distress. Although many causes of loneliness can be identified, some researchers are of the opinion that it can also be attributed to unpleasant childhood experiences that result in unfulfilled needs relating to intimacy. In this research study, the relationship between loneliness and adolescents' atti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 18 publications
2
14
0
1
Order By: Relevance
“…A meta‐analysis of loneliness in adolescence found that low levels of social support and parental expressiveness predicted loneliness in adolescence with a medium to large‐medium effect size (Mahon, Yarcheski, Yarcheski, Cannella, & Hanks, 2006). Other aspects of parental relationships associated with lower levels of loneliness include parental acceptance (Lim & Smith, 2008; Richaud de Minzi, 2006), maternal reliance and availability (Richaud de Minzi, 2006), and secure attachment (Kerns & Stevens, 1996). In contrast, high levels of leniency (Lim & Smith, 2008), parental over‐protection (Jackson, 2007), paternal pathological control (Richaud de Minzi, 2006), and a negative attitude toward one's father (Le Roux, 2009) relate to greater loneliness.…”
Section: Loneliness and Interpersonal Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta‐analysis of loneliness in adolescence found that low levels of social support and parental expressiveness predicted loneliness in adolescence with a medium to large‐medium effect size (Mahon, Yarcheski, Yarcheski, Cannella, & Hanks, 2006). Other aspects of parental relationships associated with lower levels of loneliness include parental acceptance (Lim & Smith, 2008; Richaud de Minzi, 2006), maternal reliance and availability (Richaud de Minzi, 2006), and secure attachment (Kerns & Stevens, 1996). In contrast, high levels of leniency (Lim & Smith, 2008), parental over‐protection (Jackson, 2007), paternal pathological control (Richaud de Minzi, 2006), and a negative attitude toward one's father (Le Roux, 2009) relate to greater loneliness.…”
Section: Loneliness and Interpersonal Problemsmentioning
confidence: 99%
“…Other aspects of parental relationships associated with lower levels of loneliness include parental acceptance (Lim & Smith, 2008; Richaud de Minzi, 2006), maternal reliance and availability (Richaud de Minzi, 2006), and secure attachment (Kerns & Stevens, 1996). In contrast, high levels of leniency (Lim & Smith, 2008), parental over‐protection (Jackson, 2007), paternal pathological control (Richaud de Minzi, 2006), and a negative attitude toward one's father (Le Roux, 2009) relate to greater loneliness. Lastly, extreme parental autonomy was associated with affinity for aloneness, and paternal pathological control was related to aversion to aloneness (Richaud de Minzi, 2006).…”
Section: Loneliness and Interpersonal Problemsmentioning
confidence: 99%
“…Therefore, loneliness can be linked to individual factors as well as cultural factors (Le Roux, 2009;Seepersad, Choi, & Shin, 2008). Medora, Woodward, and Larson (1987) stated that the culture and family in which an individual develops are among the important factors affecting the individual's experience of loneliness.…”
mentioning
confidence: 99%
“…This result is consistent with previous studies about shyness (Leck, ; Neto & Mullet, ; Xu, Farver & Shin, ; Zhao et al ., ), interpersonal relationships (Leck, ), and loneliness (Corsano et al ., ; Goossens & Marcoen, ; Xu et al ., ). However, some studies have found gender variations for shyness (Karevold et al ., ), interpersonal relationships (Xu et al ., ), and loneliness (Le Roux, ; Scharf et al ., ). The explanation for these inconsistent findings is that the participants varied in age.…”
Section: Discussionmentioning
confidence: 99%
“…Previous have suggested the gender differences in shyness, interpersonal relationships and loneliness (Tian, Guo, Shi et al ., ; Tian, Y., Si, Y., Meng et al ., ). For example, some studies have found that the loneliness effect is more characteristic of girls than boys (Corsano, Majorano & Champretavy, ; Goossens & Marcoen, ), however, the results have been mixed (loneliness effect is more characteristic of boys than girls; Le Roux, ; Scharf, Wiseman & Farah, ). These mixed results may be caused by the different samples with different age.…”
Section: Introductionmentioning
confidence: 99%